The Placebo and Nocebo Responses in Clinical Trials in Inflammatory Bowel Diseases - Enck, Paul; Klosterhalfen, Sibylle (Frontiers in Pharmacology, 2021)
Placebo and nocebo responses are mostly discussed in clinical trials with functional bowel disorders. Much less has been investigated and is known in gastrointestinal diseases beyond irritable bowel syndrome (IBS), especially in inflammatory bowel diseases (IBD). For the purpose of this review, we screened the Journal of Interdisciplinary Placebo Studies (JIPS) database with approximately 4,500 genuine placebo research papers and identified 9 meta-analyses covering more than 135 randomized and placebo-controlled trials (RCT) with more than 10,000 patients with Crohn´s disease (CD), and another 5 meta-analyses with 150 RCT and more than 10,000 patients with ulcerative colitis (UC). Only 3 discussed nocebo effects, especially in the context of clinical use of biosimilars to treat inflammation. The papers were critically analyzed with respect to a) the size of the placebo response in CD and UC, with its effects on clinical improvement versus maintenance of remission, and for mediators and moderators of the response identified. We will finally discuss difference and similarities of the placebo response in IBD compared to IBS, and the nocebo effect in switching from biologics to biosimilars in IBD management.